Gegen Qinlian Decoction Coordinately Regulates PPARγ and PPARα to Improve Glucose and Lipid Homeostasis in Diabetic Rats and Insulin Resistance 3T3-L1 Adipocytes - Tu, Jun; Zhu, Shuilan; Li, Bingtao; Xu, Guoliang; Luo, Xinxin; Jiang, Li; Yan, Xiaojun; Zhang, Ruiping; Chen, Chen (Frontiers in Pharmacology, 2020)
Gegen Qinlian Decoction (GQD), a well-documented traditional Chinese Medicine (TCM) formula, was reported with convincing anti-diabetic effects in clinical practice. However, the precise anti-diabetic mechanism of GQD remains unknown. In this study, the anti-hyperglycemic and/or lipid-lowering effects of GQD were demonstrated in high-fat diet with a low dose of streptozotocin-induced diabetic Sprague-Dawley rats and insulin resistance (IR)-3T3-L1 adipocytes. GQD treatment increased expression and activity levels of both PPARγ and PPARα in adipocytes, which transcriptionally affected an ensemble of glucose and lipid metabolic genes in vivo and in vitro. The results clearly indicated that GQD treatment intervened with multiple pathways controlled by concomitantly downstream effects of adipocytic PPARγ and PPARα, to influence two opposite lipid pathways: fatty acid oxidation and lipid synthesis. Antagonist GW9662 decreased the mRNA expression of Pparγ and target genes Adpn, Glut4 whereas GW6471 decreased the mRNA expression of Pparα and target genes Cpt-1α, Lpl, Mcad, Lcad, Acox1 etc. Nuclear location and activity experiments showed that more PPARγ and PPARα shuttled into nuclear to increase its binding activities with target genes. GQD decreased the phosphorylation level of ERK1/2 and/or CDK5 to elevate PPARγ and PPARα activities in IR-3T3-L1 adipocytes through post-translational modification. The increase in p-p38MAPK and SIRT1 under GQD treatment may be attributed to partially reduce PPARγ adipogenesis activity and/or activate PPARα activity. Compared with the rosiglitazone-treated group, GQD elevated Cpt-1α expression, decreased diabetic biomarker Fabp4 expression and lipid-sensor regulator SREBP-1C expression, which produced an encouraging lipid profile with TG decrease partially from combined effects on upregulated adipocytic PPARγ and PPARα activities. These results suggested that GQD improved diabetes by intervening a diverse array of PPARγ and PPARα upstream and downstream signaling transduction cascades, which jointly optimized the expression of target gene profiles to promote fatty acid oxidation and accelerate glucose uptake and utilization than PPARγ full agonist rosiglitazone without stimulating PPARα activity. Thus, GQD showed anti-diabetic/or anti-hyperglycemic effects, partially through regulating adipocytic PPARα and PPARγ signaling systems to maintaining balanced glucose and lipid metabolisms. This study provides a new insight into the anti-diabetic effect of GQD as a PPARα/γ dual agonist to accelerate the clinical use.